Predicting Academic Success for NCAA Division I Student-Athletes - Carodine, Keith; Murphey, Milledge; Orbach, Iris; Rulka, Edward T.; Frehlich, Shane; Barba, Douglas (My University, 1999)
Demographic data were obtained on the population of all freshmen student-athletes admitted to the University of Florida (UF) during 1995 (N=91). Demographic data included gender, race, age, distance from home, and several subjective measures. The researchers analyzed the relationship between UF's predictive index and student-athletes' actual Grade Point Average (GPA) and found a significant correlation (r(89)=.60). The correlation between athletes' High School GPA (HSGPA) and their UF GPA was also significant (r(89)=.61). No correlation was found between UF GPA and any of the subjective measures administered to the athletes. Recommendations are made for future testing and prediction of academic success for National Collegiate Athletic Association (NCAA) Division I student-athletes.
Keywords: freshmen; academic performance; academic predictors